A case of late-onset, thymoma-associated myasthenia gravis with ryanodine receptor and titin antibodies and concomitant granulomatous myositis. Issue 1 (December 2016) - Stefanou, M.; Komorowski, L.; Kade, S.; Bornemann, A.; Ziemann, U.; Synofzik, M.
Abstract Background Myasthenia gravis is an autoimmune neuromuscular disorder, which has only rarely been reported to co-manifest with myositis. The diagnosis of concomitant myositis in patients with myasthenia gravis is clinically challenging, and requires targeted investigations for the differential diagnosis, including EMG, autoantibody assays, muscle biopsy and, importantly, imaging of the mediastinum for thymoma screening. Case presentation This report presents a case-vignette of a 72-year-old woman with progressive proximal muscle weakness and myalgias, diagnosed with thymoma-associated myasthenia and bioptically verified granulomatous myositis, with positive autoantibody status for ryanodine receptor and titin antibodies. Conclusions The diagnosis of concurrent myositis and myasthenia gravis, especially in the presence of ryanodine receptor and titin antibodies, should lead neurologists to adopt different treatment strategies compared to those applied in myasthenia or myositis alone. Moreover, further evidence is warranted that titin and, particularly, ryanodine receptor antibodies may co-occur or be pathophysiologically involved in myasthenia-myositis cases.